Assays for enhanced activity of low efficacy partial agonists at the D(2) dopamine receptor - Lin, H (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Low efficacy partial agonists at the D(2) dopamine receptor may be useful for treating schizophrenia. In this report we describe a method for assessing the efficacy of these compounds based on stimulation of [(35)S]GTPγS binding. EXPERIMENTAL APPROACH: Agonist efficacy was assessed from [(35)S]GTPγS binding to membranes of CHO cells expressing D(2) dopamine receptors in buffers with and without Na(+). Effects of Na(+) on receptor/G protein coupling were assessed using agonist/[(3)H]spiperone competition binding assays. KEY RESULTS: When [(35)S]GTPγS binding assays were performed in buffers containing Na(+), some agonists (aripiprazole, AJ-76, UH-232) exhibited very low efficacy whereas other agonists exhibited measurable efficacy. When Na(+) was substituted by N-methyl D-glucamine, the efficacy of all agonists increased (relative to that of dopamine) but particularly for aripiprazole, aplindore, AJ-76, (−)-3-PPP and UH-232. In ligand binding assays, substitution of Na(+) by N-methyl D-glucamine increased receptor/G protein coupling for some agonists -. aplindore, dopamine and (−)-3-PPP – but for aripiprazole, AJ-76 and UH-232 there was little effect on receptor/G protein coupling. CONCLUSIONS AND IMPLICATIONS: Substitution of Na(+) by NMDG increases sensitivity in [(35)S]GTPγS binding assays so that very low efficacy agonists were detected clearly. For some agonists the effect seems to be mediated via enhanced receptor/G protein coupling whereas for others the effect is mediated at another point in the G protein activation cycle. AJ-76, aripiprazole and UH-232 seem particularly sensitive to this change in assay conditions. This work provides a new method to discover these very low efficacy agonists.